2019
DOI: 10.2525/ecb.57.93
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis and Morphology of Leaf Lettuce (<i>Lactuca sativa</i> L. cv. Greenwave) Grown under Alternating Irradiation of Red and Blue Light

Abstract: The mechanism for accelerating leaf lettuce growth by alternating irradiation of red (R) and blue (B) lights was investigated in this study. Leaf lettuce was cultivated under nine light conditions with different time ratios of R/B alternate irradiation; R0B24, R3B21, R6B18, R9B15, R12B12, R15B9, R18B6, R21B3 and R24B0. As a result, R21B3 treatment (21 hours of R irradiation and 3 hours of B irradiation, in an alternating pattern without a dark period) was determined to be the optimum condition for leaf lettuce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In closed-type plant factories with artificial light, improving production efficiency without increasing electricity costs is a challenging issue. Several recent studies have showed alternating R/B could be a promising approach to enhancing lettuce productivity and income in closed-type plant factories (Shimokawa et al, 2014;Chen et al, 2017Chen et al, , 2019Kuno et al, 2017;Takasu et al, 2019). However, the physiological reason why alternating R/B can enhance the productivity is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In closed-type plant factories with artificial light, improving production efficiency without increasing electricity costs is a challenging issue. Several recent studies have showed alternating R/B could be a promising approach to enhancing lettuce productivity and income in closed-type plant factories (Shimokawa et al, 2014;Chen et al, 2017Chen et al, , 2019Kuno et al, 2017;Takasu et al, 2019). However, the physiological reason why alternating R/B can enhance the productivity is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…'Summer Surge'), compared with lettuce grown under W light or simultaneous RB light (12 hours light : 12 hours dark) with the same daily light integrals. This phenomenon cannot be explained by a difference in day length, because alternating irradiation of red and blue (R/B) light also promoted lettuce growth relative to RB under similar day length and daily light integral (Chen et al, 2017;Kuno et al, 2017;Ohtake et al, 2018;Takasu et al, 2019). More recently, reported that an alternating interval of 1 hour promoted growth and sugar accumulation in lettuce more than that under an alternating interval of 4 hours.…”
Section: Introductionmentioning
confidence: 99%
“…From above, alternate lighting is characteristic of creating a light environment where crops are alternately irradiated by different spectral compositions. Molecular mechanisms underlying the regulation of alternate lighting on growth still remained to be discovered, whereas it is widely reported that the stimulating effects of alternate lighting are attributed to positive effects on morphology, metabolism, and photosynthesis efficiency [40,41]. Lettuce cultivated under optimal alternating blue and red light treatment tends to have a higher PA/LA (projected area/leaf area) index; meanwhile, photosynthetic efficiency was significantly enhanced [41].…”
Section: Alternate Lightingmentioning
confidence: 99%
“…Molecular mechanisms underlying the regulation of alternate lighting on growth still remained to be discovered, whereas it is widely reported that the stimulating effects of alternate lighting are attributed to positive effects on morphology, metabolism, and photosynthesis efficiency [40,41]. Lettuce cultivated under optimal alternating blue and red light treatment tends to have a higher PA/LA (projected area/leaf area) index; meanwhile, photosynthetic efficiency was significantly enhanced [41]. Besides, different monochromatic lights or spectral compositions possess varied physiological or phytochemical effects [42].…”
Section: Alternate Lightingmentioning
confidence: 99%